Structural and functional relationships of natural and artificial dimeric bovine ribonucleases: New scaffolds for potential antitumor drugs. Issue 22 (7th October 2013) - Gotte, Giovanni; Laurents, Douglas V.; Merlino, Antonello; Picone, Delia; Spadaccini, Roberta
Abstract : Protein aggregation via 3D domain swapping is a complex mechanism which can lead to the acquisition of new biological, benign or also malignant functions, such as amyloid deposits. In this context, RNase A represents a fascinating model system, since by dislocating different polypeptide chain regions, it forms many diverse oligomers. No other protein displays such a large number of different quaternary structures. Here we report a comparative structural analysis between natural and artificial RNase A dimers and bovine seminal ribonuclease, a natively dimeric RNase with antitumor activity, with the aim to design RNase A derivatives with improved pharmacological potential.